Popular television drama : critical perspectives - Bignell, Jonathan; Lacey, Stephen, 1952- (Manchester Gothic (Manchester, England), 2017)
A collection of essays that examine landmark popular television drama from the last forty years, from 'Doctor Who' to 'The Office'. Contributors focus on programmes across the range of popular genres, from sitcoms to science fiction, gothic horror and children's drama.